Syntheses of hybrid cyclopeptidyl [n]sulfanes by internal alkyl group exchange. Issue 24 (11th June 2020) - Sisto, Luke J.; Harran, Patrick G.
Graphical abstract: Highlights: Synthesis of polysulfide linked peptide macrocycles via a novel sulfide transalkylation reaction. First reported synthesis of trisulfide linked peptidyl macrocycles. Chemoselectivity and wide functional group tolerance demonstrated. Downstream strategies for elaborating macrocyclic disulfide reported. Abstract: Internal capture of the cinnamyl carbocation by tert -butylated cysteine derivatives within composite peptides affords macrocycles. The reactions proceed rapidly at room temperature and allow syntheses of mono, di and trisulfide containing ring systems. The methodology provides facile access to peptidomimetic sulfanes of varying ring size, sulfur content and constitution under non-oxidative conditions.